Arsenic Uptake, Transport, Accumulation in Rice and Prospective Abatement Strategies - A Review - Bera, Ananya; Choudhury, Bhaskar (International Journal of Experimental Research and Review, 2023)
Recent reports claim that arsenic (As) toxicity affects millions of individuals worldwide. A significant problem for rice output and quality as well as for human health is the high content of arsenic (As), a non-essential poisonous metalloid, in rice grains. Therefore, substantial research has been done on the interactions between rice and As in recent years. As rice plants uptake at the root surface is impacted by factors like radical oxygen loss and iron plaque. The absorption and movement of various As species as well as the transfer to sub cellular compartments include a multitude of transporters, including phosphate transporters and aquaglyceroporins. As III and AsV are transported into the root by phosphate transporters and intrinsic channels that mimic nodulin 26. The silicic acid transporter may have a substantial impact on how methylated As, dimethylarsinic acid (DMA), and monomethylarsonic acid (MMA), enter the root. The issue of As contamination in rice is being addressed by researchers and practitioners to the best of their abilities. Making better plans may be aided by recent research on rice that explains the processes of arsenic ingestion, transportation, and metabolism at the rhizosphere. Common agronomic techniques, such as collecting rainwater for agricultural irrigation, using natural substances that aid in the methylation of arsenic, and biotechnology methods, may be investigated in an effort to lessen the uptake of arsenic by food crops. Innovative agronomic techniques and recent research findings on arsenic contamination in rice crops will be included in this review.